Development of gyrostabiliser for rolling motion compensation - Poh, Alex Kien Boon, 1992-, author; Tang, Howe Hing, supervisor; Fakulti Kejuruteraan Mekanikal (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2017